Electro-Fenton with peroxi-coagulation as a feasible pre-treatment for high-strength refractory coke plant wastewater: Parameters optimization, removal behavior and kinetics analysis. (January 2020) - Zhou, Xin; Hou, Zilong; Lv, Lin; Song, Jingjing; Yin, Zeyang
Abstract: Electro-Fenton (EF) with peroxi-coagulation (PC) as an emerging electro-chemical advanced oxidation method has been extensively applied to treat refractory wastewater. However, the studies on the pretreatment of the raw coke plant wastewater by EF process were still lacking. In this study, a lab-scale EF system (Fe as anode and graphite as cathode) achieved the highest COD removal of 69.2% based on the preliminary experiments. The process parameters and corresponding COD removal performance were further optimized using response surface methodology (RSM) combined with Box-Behnken experimental design (BBD). The optimal conditions were obtained as: 3.2 mA cm −2 of current density, 2 h of the reaction time and 2.6 of the initial pH value, with the COD removal reaching 70.0%. Fourier infrared (FTIR), fluorescence excitation-emmission matrix (EEM) and gas chromatography-mass spectrometry (GC-MS) also revealed the degradation behaviors of dissolved organic matters (DOMs) by characterizing their structures and compositions before and after EF pretreatment, thus greatly improving the biodegradability of the wastewater. Moreover, the EF process for COD removal well followed third-order kinetics model. These findings give helpful guidance to design, optimize and control the EF process as a favourable pretreatment for actual refractory coking wastewater in practice. Graphical abstract: Image 1 Highlights: Maximum COD removal reached nearly 70% by EF process with PC. Process parameters of EF were optimized by RSM and BBD. COD removal behaviors were revealed by FTIR, EEM and GC-MS. COD removal for EF process followed three-order reaction kinetics. EF offers a suitable pretreatment option for coke plant wastewater.